Biological Control of Water Hyacinth (Eichhornia crassipes) using Neochetina spp. in the Panchaganga River, Kolhapur and its Impact - Shivam Satyawan Madrewar; Dhinwa, Sangeeta; Atharva Manish Gumphekar; Aastha Atul Deshmukh; Sayli Sujit Sarve (International Journal of Sustainable Applied Sciences, 2024)
Biological control of water hyacinth (Eichhornia crassipes) using Neochetina spp. was studied in the Panchaganga River, Kolhapur, India, where extensive infestations threatened ecological balance and human activities. Five sites along the river were monitored for six months after the introduction of Neochetina weevils. Initial water hyacinth cover averaged 85%, declining to 51% post-intervention, reflecting a 40% reduction. Water quality parameters showed significant improvements, with dissolved oxygen levels increasing by 25% and a slight rise in pH indicating favorable ecosystem conditions. Biodiversity assessments revealed an increase in species diversity indices and the return of native fish species. Statistical analysis confirmed a strong correlation (R² = 0.85) between weevil density and biomass reduction. Visual and spatial analyses supported these findings, showing reduced hyacinth density and improved river navigability. This research demonstrates Neochetina spp. as effective agents for sustainable water hyacinth management, emphasizing their role in restoring ecological health in impacted river systems. article, the method used, the results or findings and conclusions. Abstracts are written in only one paragraph